2018
DOI: 10.1002/ece3.4334
|View full text |Cite
|
Sign up to set email alerts
|

Response to joint selection on germination and flowering phenology depends on the direction of selection

Abstract: Flowering and germination time are components of phenology, a complex phenotype that incorporates a number of traits. In natural populations, selection is likely to occur on multiple components of phenology at once. However, we have little knowledge of how joint selection on several phenological traits influences evolutionary response. We conducted one generation of artificial selection for all combinations of early and late germination and flowering on replicated lines within two independent base populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…This is in contrast to studies with other species that have found significant heritabilities for flowering time (e.g. Burgess, Etterson, & Galloway, ; Franks, Sim, & Weis, ; Galloway, Watson, & Prendeville, ; Sedlacek et al, ; Van Dijk, Boudry, McCombre, & Vernet, ; Yu, Harding, Byrne, & Famula, ), and to a study indicating that there is a genetic component to flowering time in our study species (Widén & Schiemann, ). Given the low additive genetic variance for FFD found in our study, it is not surprising that observed phenotypic selection for early flowering did not correspond to genotypic selection on FFD.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to studies with other species that have found significant heritabilities for flowering time (e.g. Burgess, Etterson, & Galloway, ; Franks, Sim, & Weis, ; Galloway, Watson, & Prendeville, ; Sedlacek et al, ; Van Dijk, Boudry, McCombre, & Vernet, ; Yu, Harding, Byrne, & Famula, ), and to a study indicating that there is a genetic component to flowering time in our study species (Widén & Schiemann, ). Given the low additive genetic variance for FFD found in our study, it is not surprising that observed phenotypic selection for early flowering did not correspond to genotypic selection on FFD.…”
Section: Discussioncontrasting
confidence: 99%
“…Such correlations imply that selection might only rarely be exerted independently on the timing of a single event. Instead, selection on a focal phenological trait is often a combination of direct selection, and indirect selection acting via other phenological traits (Ehrlén, 2015; Galloway et al, 2018; Kelly, 1992; Rathcke & Lacey, 1985). Selection could also target the relative timing of phenological traits.…”
Section: Introductionmentioning
confidence: 99%
“…Phenological events are often temporally and developmentally correlated, and the timing of one event can constrain or otherwise affect the timing of subsequent events (e.g., Diggle, 1999; Mentzel et al 2006; Donohue, 2014; Galloway et al, 2018; Zacchello et al, 2020; Bucher and Römermann, 2021). Within seasons, spring and autumn phenology have been found to be positively correlated among individuals in many woody species (e.g., Crawley and Akhteruzzaman, 1988; Keenan and Richardson, 2015), with individuals both advancing their growing season and senescing earlier when exposed to experimental warming in early spring (Fu et al, 2014; Zohner and Renner, 2019).…”
mentioning
confidence: 99%